A New Approach for in vitro Imaging of Breast Cancer Cells by Anti‐Metadherin Targeted PVA‐Pyrene - Medine, E. Ilker; Odaci, Dilek; Gacal, Bahadir N.; Gacal, Burcin; Sakarya, Serhan; Unak, Perihan; Timur, Suna; Yagci, Yusuf (Wiley, 2010)
AbstractPoly(vinyl alcohol)‐pyrene‐anti‐metadherin (PVA‐Py‐(Anti‐MTDH)), a novel antibody based water soluble probe containing both fluorescent and target sites in the structure for in vitro imaging of breast cancer cells is reported here. Since breast cancer cells have an excess of MDTH protein expressed on the surface, a PVA‐Py prepared by “Click chemistry” approach is targeted by Anti‐MTDH antibody and applied to the MCF‐7 cell line. After characterization, the designed architecture was evaluated in terms of cell incorporation efficiency and compared with a non‐targeted structure (PVA‐Py). Atomic force microscopy (AFM) and fluorescence microscopy images of cells after incubation of the probe molecules were also obtained to monitor the interaction of the probes with the cancerous cells.magnified image
Keywords: Diagnostic Imaging; Immunoconjugates; synthesis; Antibodies, Neoplasm; Functionalization of polymers; Breast Neoplasms; Fluorescence; Imaging; drug delivery systems; Synthesis; Cell Line, Tumor; Humans; functionalization of polymers; Fluorescent Dyes; Pyrenes; imaging; Membrane Proteins; RNA-Binding Proteins; Drug delivery systems; Neoplasm Proteins; Polyvinyl Alcohol; Female; fluorescence; Cell Adhesion Molecules